Kepastian Hukum Harta Bersama bagi Istri Pertama dalam Perkawinan Poligami - Budianto, Willy; Sulistyarini, Rachmi (Universitas Negeri Malang, 2021)
This study aimed to analyze the legal certainty of shared property as well as the urgency of marriage agreements on the shared property for first wives in polygamous marriages. The research used the statute approach. The provisions of the law on joint property in polygamous marriage based on Article 94 of the compilation of Islamic law did not provide legal certainty to the first wife, thus the creation of a marriage treaty deed on joint property under Law Number 1 of 1974 on Marriage became one of the efforts to obtain legal certainty. The urgency of the marriage agreement on the joint property for the first wife in a polygamous marriage was related to the legal protection of the first wife when the husband was influenced by the second wife in the future.